Rotiboy to Turkey - Charukkai A/P Saigran; Daisy Mui Hung Kee; Chong Bun Yean; Chong Joyee; Hadijah Shahnaz; Huda Binti Abdus Samad (AIBPM Publisher, 2020)
Rotiboy is a Malaysian bakery chain based in Kuala Lumpur owned by Rotiboy Bakeshoppe Sdn Bhd. Rotiboy was founded in Bukit Mertajam, Penang in 1998. The founder of Rotiboy- Hiro Tan, studied economics in Universiti Malaya and he used to work as an insurance agent, property agent, airline station manager, tuition teacher and even tried mushroom farming before starting Rotiboy Bakeshoppe. He was inspired by his family to start Rotiboy and his siblings supported him in the business venture.